Extending end-to-end optical service provisioning and restoration in carrier networks opportunities, issues, and challenges. - Alanqar, W. (IEEE Communications magazine)
In this article, we address the opportunities, issues and challenges associated with end-to-end optical service provisioning and restoration in carrier networks. A number of scenarios are analyzed from a practical perspective, considering important aspects relevant to the management and control planes. Along the lines of three basic dimensions, to which we refer as locality, granularity, and ownership, we discuss the complexity associated with provisioning and restoring end-to-end optical services in regional (local scale) and national (global scale) networking scenarios. We identify a number of challenges in integrating a unified control plane solution and vendor-specific management and control planes with legacy carrier management systems.